Algologies: an artistic exploration of the entangled relationship between seaweed, women and science through a BioArt methodology - Anna Dumitriu (Applied Phycology)
This paper describes the “Algologies” project, an art project about seaweed exploring the entangled relationships between seaweed, women and science. The project was created in 2021, during the COVID-19 Pandemic, through the Living Coast Art Residency awarded by Fabrica Gallery and The Living Coast UNESCO World Biosphere and the coastline to the East of Brighton. The project plays with the Victorian word algology which used to mean the study of seaweed and its contemporary meaning as the study and medical treatment of pain and highlights the calming nature of the coastal environment during a time of collective global trauma. The “Algologies” project drew links between Victorian seaweed collectors, the use of seaweed-based agar jelly in contemporary biology, and seaweed growth as a barometer of climate change and the environment as well as a strategy for carbon capture. The transdisciplinary project fused fine art, performance and BioArt techniques with biohacking and DIY science, as well as digital technologies and resulted in a series of outputs including a public sculpture. Central to “Algologies” was the examination of the historical role of women in seaweed collection and scientific observation. In Victorian Britain, where patriarchal norms prevailed, women were often relegated to domestic roles but found opportunities for scientific engagement through activities like seaweed collecting. Figures such as Mary Philadelphia Merrifield and Anna Atkins emerged as pioneers in the study of seaweed, making significant contributions to botanical research and early photographic techniques. Notably, the project highlighted the pivotal role of Angelina (Lina) Fannie Hesse in suggesting the use of seaweed-derived agar in microbiology, a contribution that continues to impact scientific practices today. Beyond historical perspectives, “Algologies” addresses contemporary issues such as climate change and invasive species of seaweed and how the public can be engaged in these topics through art. The paper concludes by discussing the potential of seaweed for carbon capture and its role as a barometer of environmental health, as well as its use biotechnology